Tricyclic Structures in Medicinal Chemistry: An Overview of their Recent Uses in Non-CNS Pathologies - Fedi, V.; Guidi, A.; Altamura, M. (Mini Reviews in Medicinal Chemistry, 2008)
Tricyclic compounds are sometimes considered as synonima of drugs healing central nervous system pathologies, although there are some well known examples of tricyclic derivatives marketed for different indications, such as antihistamines, antivirals and antiulceratives. Following the insertion of tricyclic structures in the “privileged structures” pool, several compounds bearing a central 7-membered ring and two aryl rings at its sides have been reported, and some of them have been progressed to advanced clinical trials. An overview of tricyclic derivatives reported in the literature since 1995, that are investigated for indications not directly related to central nervous system affections, shows the potential of these structures in a broad range of therapeutical indications, going from antiviral and anticancer compounds to the therapy of cardiovascular diseases. Very recent examples confirm the usefulness of tricyclic structures for the modern medicinal chemists.
Keywords: privileged structures